PELAKSANAAN MODEL COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY (TS-TS) PADA MATA PELAJARAN IPS TERPADU KELAS VIII.B DI SMP NEGERI 34 KABUPATEN TEBO - Zuhrotul Viafarida; Meldawati Meldawati; Ranti Nazmi (Universitas Pahlawan, 2021)
This research is motivated by the implementation of the discussion that has not been optimal. The purpose of the study was to describe the implementation and constraints of the Two Stay Two Stray (Ts-Ts) Cooperative Learning Model in Integrated Social Studies Subjects Class VIII.B at SMP Negeri 34 Tebo Regency. The method used is descriptive qualitative. The results of the study: 1) The division of groups has been carried out but there are groups that have 3 members, ideally each group has 4 people. 2) The distribution of materials has been carried out. Intragroup discussions have been carried out. 3) The implementation of Two Stray, has not been fully implemented. The problem was that there was one meeting that did not carry out Stray activities. 4) Implementation of Two Stay. The problem is that there are two groups where only one member stays, ideally there are two members who stay (Stay). 5) Discussion of the results of the Two Stay Two Stray (TS-TS) activity was not carried out. The presentation activity has been carried out. Activities of the Two Stay Two Stray Type Cooperative Learning (TS-TS) model was not fully implemented and there are still obstacles in its implementation.